Fatal intimate partner violence against women in Portugal: a forensic medical national study - Pereira, Ana Rita (2013)
Intimate partner violence (IPV) is an important cause of women's health and socio-familial severe problems, the most extreme being the victims' homicide. This is the first nationwide Portuguese autopsy-based and judicial-proven study about female intimate partner homicide. At least 62 women over 15 years old were killed by current or former men-intimate partners, corresponding to an IPV-related female mortality rate of 0.44/100.000 women; intimate partner violence was the reason of homicide in 60.8% of all autopsied women. The typical Portuguese victim showed to be a young adult woman, employed, killed by a current husband in a long-term relationship, usually with children in common and with a history of previous IPV. The typical Portuguese perpetrator showed to be older than the victim, employed, owning a firearm and without criminal records. At the time of the fatal event 59.7% of the relationships were current. In 57.9% of the former relationships women were killed during the 1st year after its terminus. Near half of the perpetrators attempted or committed suicide afterward. Most women were killed by gunshot wounds (45.2%), especially in the thorax (48.4%), with multiple fatal injuries; 56.5% also presented non-fatal injuries. The detection of prior IPV and the risk evaluation seems to be fundamental to decrease these fatal outcomes, but also, the prevention of perpetrators' alcohol abuse and carrying weapons. This work emphasizes the need to deepen the research on this issue, aiming to contribute to prevent both fatal and non-fatal IPV-related cases.